Re-discussion of servitization strategy and firm performance - Li, Kang; Wang, Jinfeng; Feng, Lijie; Zhu, Lei (Frontiers in Psychology, 2022)
Servitization innovation is critical for manufacturing firms to strengthen their sustainable competitive advantage in a dynamic business environment. Current research on the relationship between servitization and firm performance has matured, but many conclusions remain divergent. That can not only hinder the development of servitization theory, but also make manufacturers lack a scientific basis for deciding whether to develop servitization. Thus, this study aims to systematically analyze the quantitative research results in this field through Meta-analysis methods to reveal the reasons for the disagreement. After collecting 59 independent articles on servitization and firm performance, this study performed statistical analysis using Meta-analysis. Then, the relationship between servitization and firm performance was explored, as well as the effects of different potential moderating variables. The moderate positive relationship between servitization strategies and their different orientations and firm performance is found. For the moderating variables, the servitization strategy has a more significant effect on non-financial performance. And they are more correlated when there are mediator variables. The impact of firm servitization transformation in developing regions is better than in developed areas. A stable market environment is more beneficial to the servitization transformation. The transformation effect of high-tech manufacturing is better than that of traditional manufacturing. And the transformation effect of large companies is better than that of small and medium-sized companies.